Penggunaan Agregat Kasar Sungai Dampala Kabupaten Morowali Sebagai Bahan Campuran Beton Berongga - Putra Imanuel; Benny Kusuma; Luciana Buarlele (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The use of concrete in Indonesia is increasingly widespread due to the main reasons that underlie concrete as the main choice in construction work compared to wood. Hollow concrete is concrete without fine aggregate and only consists of coarse aggregate, cement and water. The specimen in the form of a cylinder measuring 15 x 30 cm is then tested with a predetermined concrete age of 28 days. From the test results obtained a compressive strength of 14.343 MPa. The results of the permeability test for hollow concrete at the age of 28 days were 2.040 cm/sec. The results of the pore volume test on hollow concrete with an age of 28 days were 25.157%. From the results of the test above, the characteristics of hollow concrete (compressive strength, permeability, and pore volume) obtained using coarse aggregate from the Dampala river, Morowali Regency in the compressive strength test obtained a compressive strength value of 14, 434 Mpa so it does not meet the compressive strength plan i.e. 20 MPa. Permeability testing and pore volume obtained from this test are satisfactory.